Superhydrophobic surfaces - Karapanagiotis Ioannis; Manoudis Panagiotis (Journal of the Mechanical Behavior of Materials, 2012)
Superhydrophobicity – also known as water repellency – has recently attracted considerable attention because of its numerous potential applications. However, the fundamental concepts and equations describing the wettability of superhydrophobic surfaces have been known since the 1940s. These concepts are reviewed and discussed in the present feature article in light of the recent developments. Furthermore, the potential use of water-repellent siloxane-nanoparticle composites for surface protection and consolidation of stones and mortars used in outdoor objects of cultural heritage is investigated. Finally, it is shown that the wettability of the composite surfaces can be predicted by the Cassie-Baxter equation.